CESifo World Economic Survey November 2014 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Erdal Yalcin (CESifo World Economic Survey, 2014)
World Economic Climate: World economic climate deteriorates - Economic Expec tations: Economic expectations less positive - Inflation: Inflation expectations remain low - Currencies: US dollar expected to rise - Interest Rates: Interest rates look set to remain stable - Special Topic: Impact of the Transatlantic Trade and Investment Partnership on partners and third parties
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies